Different doses of pFSH are effective to promote follicular growth, superovulatory response, and embryo yield in White Dorper ewes - Dias, J. H.; Vergani, G. B. [UNESP]; Gonçalves, J. D. [UNESP]; Oliveira, T. A.; Penitente-Filho, J. M.; Pereira, V. S.A.; Esteves, S. N.; Garcia, A. R.; Batista, R. I.T.P.; Oliveira, M. E.F. [UNESP]; Souza-Fabjan, J. M.G.; Fonseca, J. F. (Elsevier, 2023)
This study evaluated the effect of 250, 333, or 400 IU of a commercial porcine stimulating-follicle hormone (pFSH) on follicular growth, superovulatory (SOV) response, and embryo yield in White Dorper sheep. Ewes received an induced-ovulation protocol (D0 = progesterone (P4) device insertion) and superovulation starting 60 h before P4 withdrawal (D9), which consisted of six decreasing doses of 250 IU (G250; n = 15), 333 IU (G333; n = 15), or 400 IU (G400; n = 14) of pFSH. Ewes also received 50 µg of gonadotropin-releasing hormone (GnRH) analog on D10 and 300 IU of hCG on D13. Ewes were mated and submitted to non-surgical embryo recovery (NSER). Ultrasound evaluations were performed on D6, D7, D8, D9, and D16. The overall responding donor rate (≥3 CL) was 86.4% (38/44). The mean number of large follicles was higher (P < 0.05) in all groups on D8 (6.2 ± 0.9, 7.7 ± 0.9, and 8.3 ± 1.1) and D9 (11.1 ± 0.6, 10.4 ± 1.0, and 11.5 ± 0.9). Non-surgical embryo recovery procedures were successfully performed in 60.5% (23/38) of females. The CL count in successfully flushed ewes was greater (P < 0.05) in G333 (12.7 ± 2.3) and G400 (12.0 ± 1.3) than in G250 (6.0 ± 1.1). The recovery rate (44.4%, 57.3%, and 50.0%) and numbers of transferable embryos (2.3 ± 1.1, 6.1 ± 2.6, and 4.5 ± 1.3) did not differ (P > 0.05) among groups. All protocols were efficient in promoting follicular growth and adequate superovulatory response and embryo yield.
Keywords: Follicular dynamics; FSH; MOET; Ovarian superestimulation; Ovine